Innovations in Pediatric Rehabilitation Therapies: Using Biomedical Technology to Improve Mobility in Children with Neuromuscular Disabilities - Brayan Ramiro Barreno Padilla; Andrés Felipe Rodríguez Galeano; Manuel Franco-Arias (International Journal of Medical Toxicology and Legal Medicine, 2024)
Neuromuscular disabilities affect children's mobility, limiting their physical and social development. Innovations in biomedical technology, such as exoskeletons and neuromuscular stimulation devices, are revolutionizing pediatric rehabilitation therapies. This article explores the impact of these technologies on the mobility of children with neuromuscular disabilities. Through an analysis of recent studies, the advantages and limitations of these technological therapies are examined, highlighting the advances in the design and application of biomedical devices and their effects on the quality of life of patients. The results suggest that biomedical technology can significantly improve motor functionality in this population, although longitudinal studies are still required.